Fourier interferometry of multi-layer sample using wavelength tuning and partially negative window. (February 2021) - Kim, Yangjin; Bae, Wonjun; Moon, Young Hoon; Hibino, Kenichi; Mitsuishi, Mamoru
Highlights: Formulation of bias phase error occurring during wavelength tuning. Development of 4 N – 1 algorithm that can eliminate the bias phase error. Numerical error analysis of 4 N – 1 algorithm with comparisons to other algorithms. Measurement of thickness and surface of LNB wafer using 4 N – 1 algorithm and Fizeau interferometer. Abstract: When measuring the thickness of a transparent plate using wavelength tuning-based phase modulation fringe analysis, the nonlinearity of the phase modulation can cause both a nonuniform phase error and a bias phase error. In this study, a method of eliminating the bias phase error using the characteristic polynomial theory was developed and a flexible 4 N − 1 algorithm, consisting of a partially negative window and a discrete Fourier transform term, was constructed. The behaviors of the 4 N − 1 algorithm were visualized in the frequency domain. The error compensation ability was estimated by comparing it to conventional algorithms. The thickness and surface profile of a lithium niobate wafer were simultaneously measured using a Fizeau interferometer and the proposed 4 N − 1 algorithm. The experimental results showed that the 4 N − 1 algorithm performs better than other algorithms in terms of the repeatability error and suppression of the bias phase error.